Socialization and education on utilization of UAV (Unmanned Aerial Vehicles) and Village Community Economic Empowerment Through Silvofishery in Kedai Damar Village, Serdang Bedagai, North Sumatra - Arinah, Hafizah; Anggraini, Novita; Purba, Mhd Adanan; Afifah, Nur; Abdillah, Manda Rizky; Ambarita, Winda Lestari; Akbar, Muhammad Syawal; Dimas, Muhammad; Putri, Intan Novita Dwi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The service team carried out was entitled "Utilization of UAV (Unmanned Aerial Vehicle) for Village Mapping and Economic Empowerment of Village Communities Through Silvofishery in Kedai Damar Village, " Serdang Bedagai, North Sumatra.PKM activities with this partnership scheme focus on the field of information technology with geospatial information systems through drones for mapping village administrative centers. Some people in Kedai Damar Village have a livelihood as casual daily laborers, farmers, and entrepreneurs. Partner problems that become priority are: (1) There is no mapping of the central area of ​​the village administration, and (2) Lack of community knowledge of land use through silvofishery. Therefore, the solution offered is using drone technology (Unmanned Aeriel Vechiel) for mapping village administration and increasing the skills and insight of the village community by training on land use based on the silvofishery system as a solution to improving the economy of the Kedai Damar Village community. The main objective of this service is to map Kedai Damar Village's administrative center. Immigrant communities can utilize this map as a public service. Another goal is to train the community by increasing community skills through silvofishery-based land use for catfish and eel cultivation and reforestation with guava, jengkol, and petai seeds.